THE DEVELOPMENT OF ENRICHMENT BOOK TO MINIMIZE THE OCCURRENCE OF MATHEMATICAL FALLACY - Sukardi
Mathematical fallacy refers to a misleading argument or belief based on a certain error, often not easily detected and frequently used to support a line of proof leading to incorrect conclusions. This phenomenon frequently occurs in classroom learning without being realized by either students or teachers. Mathematical fallacy can hinder deep understanding and problem-solving abilities, both for teachers and students, as it is closely related to the maturity of understanding of certain mathematical concepts. Furthermore, one factor that potentially contributes to the occurrence of mathematical fallacy in classroom learning is the teacher. This research aims to develop an enrichment book aimed at minimizing the occurrence of mathematical fallacies for secondary school mathematics teachers. The developed enrichment book also was tested for its validity, practicality, and effectiveness in achieving this goal. This research uses a research and development approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used in this research include expert validation sheets for content and graphics, user response questionnaires, initial test sheets, final test sheets, and honesty surveys. Before the enrichment book development began, researcher identified problems in the field, namely the high potential for mathematical fallacy in classroom learning. This was measured by the average low performance of teachers in completing the pre-test previously given. In this analysis phase, the researcher selected 20 mathematics teachers at the junior or senior high school level from various regions in Indonesia as research subjects. The sample selection was carried out using a simple random sampling technique with a willingness form as the research subject, which was distributed in a WhatsApp group consisting of mathematics teachers participating in LaTeX training. Subsequently, the research was conducted by designing the enrichment book, which included determining the book title, designing the book cover, layout, and outline. In terms of content, the developed enrichment book consists of six chapters. Chapter I, titled "Introduction," discusses mathematics in general and introduces mathematical fallacies. Chapters II through VI successively discuss mathematical fallacies in arithmetic, algebra, geometry, calculus, and statistics. The content presentation in Chapters II through VI always begins with the history of each field, followed by the scope of the subject, and then continued with cases of mathematical fallacies that occur. After producing the initial draft of the enrichment book, the research continued with validating the enrichment book by 11 subject expert validators and 1 graphic expert validator. The results of the subject and graphic expert questionnaire scores indicated that the developed enrichment book was categorized as very good in terms of validity. Revisions based on comments and suggestions from the validators were then made by the researcher. In the implementation phase, the validated and revised book was tested on the research subjects. The trial was conducted over one month. After the trial period was completed, the research subjects were asked to fill out a user response questionnaire. Then, a post-test and an honesty survey were given to them. The analysis of the user response questionnaire indicated that the enrichment book was declared practical with a very good category. Furthermore, the data processing results of the pre-test and post-test scores showed that 1 person obtained a normalized gain score in the low category, 13 people in the medium category, and the remaining 6 people in the high category, with the honesty level of the research subjects being 94.8%. Furthermore, the overall average normalized gain score was 0.59. Thus, it was concluded that the developed enrichment book was considered quite effective in minimizing mathematical fallacies.